2004
DOI: 10.1021/ie030695n
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Gallium from Bayer Liquor Using Chelating Resins in Fixed-Bed Columns

Abstract: In recent times, resins with chelating ligands (hydroxamic acids, in particular) have received considerable attention owing to their selective adsorption of gallium from sodium aluminate liquor, commonly known as Bayer liquor. This paper deals with the synthesis of a chelating ion-exchange resin as well as the studies carried out on the resin to ascertain its loading capacity for gallium, kinetics, stability toward acid and alkali besides its recyclability. The paper also gives a description of the ion-exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…These results are presented in Table 8 . It may be seen that RCP and ACP are competitive to synthetic ion exchange resin showing adsorption capacities of 7.32 and 7.61 mg/g, respectively, which are higher than that of reported value (6.0 mg/g) on resin with hydroxamic acid ligand [ 3 ].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These results are presented in Table 8 . It may be seen that RCP and ACP are competitive to synthetic ion exchange resin showing adsorption capacities of 7.32 and 7.61 mg/g, respectively, which are higher than that of reported value (6.0 mg/g) on resin with hydroxamic acid ligand [ 3 ].…”
Section: Resultsmentioning
confidence: 88%
“…It finds significant applications in the semiconductor industry through use of gallium arsenide and gallium nitride. Gallium is classified as a “strategic” metal, since it is used in high-tech gadgets like microwave transceivers, DVDs, laser diodes in CDs, and so forth and defence-related activities [ 1 3 ]. Gallium nitrate and gallium citrate are used in medical imaging as radio contrast agents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…to remove Si, Ga, and V from the Bayer liquor. [7][8][9][10][11][12][13] Recently, it has been reported that a kind of lithium-containing bauxite used for alumina production suffers from lithium enrichment (50-100 mg L À1 ) in the Bayer liquor, which has seldom been encountered in previous studies. 14,15 Due to high dissolubility of most lithium salts, it is hard to remove lithium impurities by precipitation/co-precipitation methods from the Bayer liquor.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies document the successful recovery of metals from ion-exchange resins and subsequent resin regeneration and reuse (e.g. McKevitt and Dreisinger 2009;Nikoloski and Ang 2014;Petruzzelli et al 1995;Riveros et al 2008;Sarkar et al 2007;Selvi et al 2004). In addition to Sb removal from aqueous solution to extremely low residual concentration, an advantage of ion exchange resin use for mine water purification is the relative ease of recovery of adsorbed ions.…”
Section: Potential For Sb Recoverymentioning
confidence: 99%